Translating Illocutionary Verbs of Quick Chat in Mobile Legends Bang Bang - Dina Isnaeni Putriaji; Widyastuti (e-Journal of Linguistics, 2023)
The global enthusiasm for online games requires the game developer andpublisher to provide various language translations. The players require tocommunicate and strategize well to win the match. The Quick Chat used byMLBB players to communicate and build strategy must be translated asappropriate to the context. This research investigated the translationtechniques applied to the Quick Chat verb in MLBB. Translation techniquesare important for transmitting the message from ST to TT. Since QuickChat primarily consists of verbs, this research focuses on the translation ofillocutionary verbs of Quick Chat in MLBB. This research appliedqualitative methods. Directive and assertive are the two illocutionary verbsfound in 30 randomly selected data. Furthermore, five translation techniquesapplied in the illocutionary verbs are the literal, transposition, amplification,modulation, and reduction technique. Additionally, this study also revealsthat the transposition technique changes the type of illocutionary acts fromdirective to assertive. Therefore, the selection of translation techniquesshould be appropriate to preserve the message and purpose of the QuickChat.